Biotechnological Potential of Extremophiles: Environmental Solutions, Challenges, and Advancements - Fabrizia Sepe; Ezia Costanzo; Elena Ionata; Loredana Marcolongo (Biology)
Extremophiles are microorganisms capable of living on Earth in ecological niches characterized by peculiar conditions, including extreme temperatures and/or pH, high salt concentrations, and the presence of heavy metals. The development of unique structural and functional adaptation strategies has stimulated an increasing scientific interest since their discovery. The importance of extremophiles lies in their exploitability in significant bioprocesses with several biotechnological applications and their role as a fundamental source of numerous high-value-added biomolecules. This review aims to examine the diversity and specificities of extremophilic archaea and bacteria, with particular emphasis on their potential applications and development in biotechnology and biomedicine. The use of extremophiles and their extremozymes has allowed applications in several fields, such as bioremediation, sustainable agriculture, the recovery of bioactive molecules for use in bioenergy, biomedicine, and nanoparticle production. The comprehension and exploitation of the complex molecular mechanisms that enable life in extreme environments represent a challenge to mitigate current climate change problems and to invest in sustainable development towards a green transition.